2011
DOI: 10.1002/mnfr.201000292
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of EGF‐induced tumor cell migration and matrix metalloproteinase‐9 expression by capsaicin via the inhibition of EGFR‐mediated FAK/Akt, PKC/Raf/ERK, p38 MAPK, and AP‐1 signaling

Abstract: Capsaicin inhibited the EGF-induced invasion and migration of human fibrosarcoma cells via EGFR-dependent FAK/Akt, PKC/Raf/ERK, p38 mitogen-activated protein kinase (MAPK), and AP-1 signaling, leading to the down-regulation of MMP-9 expression. These results indicate the role of capsaicin as a potent anti-metastatic agent, which can markedly inhibit the metastatic and invasive capacity of fibrosarcoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 37 publications
3
67
0
1
Order By: Relevance
“…1B) enabling multiple simultaneous observations. The tumor cells invade in 3D in response to externally applied growth-factor gradients [e.g., epidermal growth factor (EGF) (26,27)] or paracrine signals by the endothelial cells or other stromal cell types [e.g., macrophages (28,29)]. On the 3D ECM-endothelial channel interface, a continuous endothelial monolayer is formed, which enables the observation of intravasation across a hollow vascular lumen, and allows for access to the basal and apical endothelial surfaces through the microchannels.…”
Section: Resultsmentioning
confidence: 99%
“…1B) enabling multiple simultaneous observations. The tumor cells invade in 3D in response to externally applied growth-factor gradients [e.g., epidermal growth factor (EGF) (26,27)] or paracrine signals by the endothelial cells or other stromal cell types [e.g., macrophages (28,29)]. On the 3D ECM-endothelial channel interface, a continuous endothelial monolayer is formed, which enables the observation of intravasation across a hollow vascular lumen, and allows for access to the basal and apical endothelial surfaces through the microchannels.…”
Section: Resultsmentioning
confidence: 99%
“…6). c-Jun and c-Fos interact to form the activated heterodimeric AP-1 transcriptional factor, which can bind to specific sequences in the promoter regions of many genes, such as N-cadherin [61]. In addition, it was found that both c-Jun and c-Fos occupy the AP-1 site in the N-cadherin promoter in response to UTP, and that the absence of only one AP-1 binding site in the human N-cadherin promoter is sufficient to block the UTP-induced promoter activity of N-cadherin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Akt and ERK pathways were closely correlated with cell invasion and migration (13,14,(24)(25)(26), the effect of ERK and Akt in the RANKL/ RANK pathway was evaluated. The results showed that sRANKL promoted the activation of ERK and Akt in MCF-7 cells (Fig.…”
Section: Erk and Akt Were Involved In Rankl-induced Breast Cancer Celmentioning
confidence: 99%
“…Findings of previous studies have shown that AKT and ERK1/2 were closely correlated with cell migration (13,14,(24)(25)(26). In mouse B16F10 melanoma cells, pretreatment with the inhibitor of PI3K, PKC, PLC or MEK1/2 suppressed .01 indicate significant difference compared with the control.…”
mentioning
confidence: 94%